Detection of volatile metabolites of garlic in human breast milk - Scheffler, Laura; Sauermann, Yvonne; Zeh, Gina; Hauf, Katharina; Heinlein, Anja; Sharapa, Constanze; Büttner, Andrea (Metabolites, 2016)
The odor of human breast milk after ingestion of raw garlic at food-relevant concentrations by breastfeeding mothers was investigated for the first time chemo-analytically using gas chromatography−mass spectrometry/olfactometry (GC-MS/O), as well as sensorially using a trained human sensory panel. Sensory evaluation revealed a clear garlic/cabbage-like odor that appeared in breast milk about 2.5 h after consumption of garlic. GC-MS/O analyses confirmed the occurrence of garlic-derived metabolites in breast milk, namely allyl methyl sulfide (AMS), allyl methyl sulfoxide (AMSO) and allyl methyl sulfone (AMSO2). Of these, only AMS had a garlic-like odor whereas the other two metabolites were odorless. This demonstrates that the odor change in human milk is not related to a direct transfer of garlic odorants, as is currently believed, but rather derives from a single metabolite. The formation of these metabolites is not fully understood, but AMSO and AMSO2 are most likely formed by the oxidation of AMS in the human body. The excretion rates of these metabolites into breast milk were strongly time-dependent with large inter-individual difference
Keywords: garlic; human milk; gas-chromatography mass-spectrometry; allyl methyl ulfide; allyl methyl sulfoxide; allyl methyl sulfone